Coping strategies related to food insecurity at the household level in Bangladesh - Dil Farzana, Fahmida; Rahman, Ahmed Shafiqur; Sultana, Sabiha; Raihan, Mohammad Jyoti; Haque, Md Ahshanul; Waid, Jillian L.; Choudhury, Nuzhat; Ahmed, Tahmeed J. (© 2017 Public Library of Science, 2018)
This article was published in the PLoS ONE [© 2017 Farzana et al.] and the definitive version is available at: https://doi.org/10.1371/journal.pone.0171411 The Journal's website is at: http://journals.plos.org/plosone/article?id=10.1371/journal.pone.0171411